Application of a non-noble Fe-N-C catalyst for oxygen reduction reaction in an alkaline direct ethanol fuel cell - Osmieri, Luigi; Escudero-Cid, Ricardo; Monteverde Videla, Alessandro H.A.; Ocón, Pilar; Specchia, Stefania (Renewable energy, 2018)
A Fe-N-C non-noble metal (NNM) catalyst for oxygen reduction reaction (ORR) was prepared via hard templating method using Fe(II)-phthalocyanine. Its electrochemical behavior towards the ORR was tested in alkaline conditions using cyclic voltammetry (CV) and rotating disk electrode (RDE) techniques. The kinetics of the reduction of the adsorbed oxygen, the selectivity, and the activity towards hydrogen peroxide reduction reaction (HPRR) were investigated. The ethanol tolerance and the stability in alkaline conditions were also assessed with the purpose to verify the good potentiality of this catalyst to be used in an alkaline direct ethanol fuel cell (DEFC). The results evidence that the ORR occurs mainly following the direct 4 e– reduction to OH−, and that the Fe-N-C catalyst is highly ethanol tolerant and shows a promising stability. The alkaline DEFC tests, performed after the optimization of the ionomer amount used for the preparation of the catalyst ink, show good results at low-intermediate currents, with a maximum power density of 62 mW cm−2. The initial DEFC performance can be partially recovered after a purge-drying procedure. [Display omitted] •The ORR kinetics of a Fe-N-C catalyst was investigated using cyclic voltammetry.•Fe-N-C catalyst is more active towards O2 reduction than H2O2 reduction.•Fe-N-C catalyst is ethanol tolerant and shows good durability in RDE.•Performance of alkaline DEFC varies using different ionomer wt. % at cathode.•Short-term DEFC durability was preliminary assessed.